Coastal and Marine Pollution : Source to Sink, Mitigation and Management - Vithanage, Meththika; Samarasekara, Sameera M; James, Bryan D.; Reddy, Christopher M. (John Wiley & Sons, 2025)
"Marine environments are generally understood as aquatic ecosystems with high contents of dissolved salts, including the open ocean and coastal ecosystems such as estuaries. According to the United Nations Convention on the Law of the Sea, the 'marine environment' is defined as "the physical, chemical, geological and biological components, conditions and factors which interact and determine the productivity, state, condition, and quality of the marine ecosystem, the waters of the seas and the oceans and the airspace immediately above those waters, as well as the seabed and ocean floor and subsoil thereof" (Valencia and Akimoto, 2006). Coastal environments are described as transition zones where the terrestrial watersheds make close interactions with the open ocean and the atmosphere (Lavalle et al., 2011; Werner and Blanton, 2019). Accordingly, coastal environments include some of the most complex and dynamic ecosystems on earth such as estuaries, bays, coral and other biogenic reefs, shallow near-shore waters, tidal wetlands, mudflats, mangrove swamps, and saltmarshes (Cowie and Woulds, 2011; Cabral et al., 2019; Nunes and Leston, 2020)"--